Contraception among Medical and Paramedical Students in Cotonou, Benin in 2016: Knowledge and Practices - TONATO BAGNAN, Josiane Angeline; OGOUDJOBI, OGOURINDÉ MATHIEU; LOKOSSOU, Mègnissè Sèna H. S.; OBOSSOU, Awadé Afoukou Achille; ABOUBAKAR, MOUFALILOU; PERRIN, RENÉ-XAVIER (My University, 2017)
Introduction: Contraception is a mean of preventing unwanted pregnancies and thus prevents induced abortions and its complications. Objective: To assess the knowledge and practices of future health workers on contraception. Methods: This was a survey carried out in Cotonou (Benin) by the students of the Medical Training and Research Unit at the Faculty of Health Sciences (FSS) and the Institut Médico-Sanitary (INMeS). Results: The survey involved 525 students, including 259 males and 266 females. The average age of students was 21 ± 2 years (15-31 years). Almost all students (9/10) had at least one contraceptive method. The rate of contraceptive use was 86.5%. The contraceptive method used by males students was the male condom, unlike females students who used natural methods and emergency contraception. The age, religion and marital status of the students had no influence on the use of contraception. The reasons for non-use of contraceptive methods were mainly the lack of knowledge about contraception (62.5%) and fear of side effects (20.0%). Conclusion: Knowledge and practice of contraception are appreciable in medical and paramedical training in Cotonou.
Keywords: Contraception; Student; Knowledge; Practice